Analisis Penggunaan Media Digital Canva Interaktif dengan Pendekatan Deep Learning terhadap Motivasi Belajar Siswa Kelas IV SD - Anastasia Christina Damayanti; Vivi Rulviana; Tiara Intan Cahyaningtyas (Prosiding Konferensi Ilmiah Dasar, 2026)
This study analyzes the use of interactive Canva digital media combined with a deep learning approach on the learning motivation of fourth-grade elementary school students. The research employed a qualitative case study conducted at SDN Sirapan 01, Madiun Regency. Data were collected through observation, interviews, and documentation involving a fourth-grade teacher and students, then analyzed through data reduction, data display, and conclusion drawing, and validated through source, method, and time triangulation. The results indicate that interactive Canva digital media integrated with a deep learning approach fosters active, interactive, and student-centered learning. Interactive Canva featuring images, videos, animations, and quizzes effectively enhances student attention, focus, and engagement, while the deep learning approach is implemented through meaningful, mindful, and joyful learning activities such as discussion, exploration, and reflection. Students' learning motivation improved, shown through enthusiasm, persistence, interest, active participation, and self-confidence.